PENGARUH KARAKTERISTIK AKUN SOCIAL MEDIA INFLUENCER TERHADAP NIAT UNTUK MENGIKUTI AKUN DAN SARAN PADA MEDIA SOSIAL TIKTOK - Rizdki Wicaksono Putra; Indira Rachmawati (Jurnal Ilmiah Global Education, 2023)
Internet users are increasing every year which makes the use of social media also increase. The use of social media by consumers is increasing and one of the reasons is to seek information as a basis for decision making, so that someone who can make an impact appears, namely social media influencer (SMI). Information provided by social media influencers currently has a high level of trust and data shows that 62% of consumers in Indonesia make purchases based on advice given by influencers. One of the social media influencers who has the highest followers on several social media and has influence on his followers in the field of fashion and beauty, namely Tasya Farasya. However, in the midst of its popularity, some followers complained about declining account publications. This study aims to determine whether there is a positive influence related to the account publication features (originality, quality, quantity, humor) on followers' intentions to continue following account publications and advice. A total of 385 respondents who were followers of the tiktok account were used. Quantitative methods are used with analysis structural equation modelling (SEM). SmartPLS 3.0 software was used for data analysis. The results of this study indicate that the publication of humor-based content is an important factor in retaining followers. and the value of uniqueness is also considered to increase influence capacity and drive the effectiveness of influencer marketing campaigns with brands.